Adhesive composition, adhesive film, connection structure, and method for producing same
By adding particles of specific metal compounds and compounds containing nitrogen-containing aromatic heterocyclic rings to the binder of the radical curing system, the problem of insufficient saline resistance in a brine environment is solved, and higher saline resistance and connection reliability are achieved.
Patent Information
- Application Number
- CN202380065476.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-15
- Filing Date
- 2023-09-13
- Publication Date
- 2025-05-02
AI Technical Summary
The binders of the existing radical curing system exhibit low brine resistance in a brine environment and are prone to peeling at the connection.
The binder is formulated to improve its brine resistance by adding particles with specific metal compounds and compounds containing nitrogen-containing aromatic heterocycles to the binder composition of the radical curing system.
The salt water resistance of the adhesive in the brine spray test is significantly improved, the peeling of the connection part is reduced, and the reliability of the connecting structure is enhanced.
Smart Images

Figure CN119923449A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an adhesive composition, an adhesive film, a connection structure and a manufacturing method thereof. Background Art
[0002] In recent years, various adhesives have been used in the fields of semiconductors, liquid crystal displays, etc. to fix electronic parts or connect circuits. In these applications, high density or high precision has gradually progressed, and high adhesion or reliability is required for adhesives. In particular, in the connection between a liquid crystal display and a tape carrier package (TCP), the connection between a flexible printed circuit substrate (FPC) and a TCP, the connection between an FPC and a printed circuit board, the connection between a semiconductor silicon chip and a substrate, the connection between an FPC and a touch panel module, and the connection between FPCs, an anisotropic conductive adhesive containing conductive particles is used as a circuit connection material.
[0003] As such adhesives, in recent years, free radical curing system adhesives (for example, free radical curing system adhesives using (meth) acrylate derivatives and peroxides as free radical polymerization initiators) have attracted attention. With regard to free radical curing systems, since free radicals as reactive species have very high reactivity, they can be cured in a short time, and the adhesive exists stably below the decomposition temperature of the free radical polymerization initiator, so it is a curing system that takes into account both low-temperature short-time curing and storage stability (for example, storage stability near room temperature). In addition, since the free radical curing system does not use ionic polymerization such as epoxy curing systems such as cationic-epoxy curing systems and anionic-epoxy curing systems, it has the advantage of excellent corrosion resistance when subjected to a conventional high temperature and high humidity test compared to the epoxy curing system. On the other hand, in the adhesives of the cationic-epoxy curing system or the anionic-epoxy curing system, the corrosion can sometimes be suppressed by adding metal hydroxides or metal oxides, etc. (for example, refer to the following patent documents 1 to 4).
[0004] Previous technical literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2006-199778
[0007] Patent Document 2: Japanese Patent Application Publication No. 2012-46756
[0008] Patent Document 3: Japanese Patent Application Publication No. 2012-46757
[0009] Patent Document 4: Japanese Patent Application Publication No. 2012-41544
[0010] Patent Document 5: International Publication No. 2009 / 063827 Summary of the invention
[0011] Technical issues to be solved by the invention
[0012] In recent years, wearable terminals (worn terminals) and display terminals (smartphones, tablet computers, smart watches, etc.) with high durability as added value have been increasing. For circuit connection materials used as components of these terminals, even when the structure obtained by using the circuit connection material is exposed to salt water, such as sweat and seawater, excellent connection reliability is required. That is, in such circuit connection materials, excellent salt water resistance (resistance to salt water) is required.
[0013] An object of the present invention is to provide an adhesive composition capable of obtaining a connection structure having excellent salt water resistance, an adhesive film using the adhesive composition, a connection structure, and a method for producing the same.
[0014] Means for solving technical problems
[0015] As methods for evaluating salt water resistance (resistance to salt water), JIS Z 2371 (2000 Salt spray test method); ISO 9227 (2006 Corros ion tests inartificial atmospheres-Salt spray tests.); a method of immersing in 5% salt water; a method of immersing in salt water and then placing in a high temperature and high humidity tank, etc. are used. As a result of verification by the present inventors, it was found that when the test related to salt water resistance was performed on a connected structure obtained by connecting using an adhesive composition, the adhesive composition of the free radical curing system was more likely to peel off at the connection part than the adhesive composition of the cation-epoxy curing system or the anion-epoxy curing system, and the salt water resistance was low.
[0016] In this regard, the present inventors have repeatedly conducted research and found that by combining particles containing a specific metal compound and a compound having a nitrogen-containing aromatic heterocycle in an adhesive composition of a free radical curing system, the salt water resistance of the connected structure in the above-mentioned salt water spray test can be significantly improved, thereby completing the present invention.
[0017] That is, the present invention includes the following aspects.
[0018] [1] An adhesive composition comprising a radical polymerizable compound, a radical polymerization initiator, a compound having a nitrogen-containing aromatic heterocycle, and particles containing at least one metal compound selected from the group consisting of metal hydroxides and metal oxides.
[0019] [2] The adhesive composition according to [1], wherein
[0020] The nitrogen-containing aromatic heterocyclic ring is at least one selected from the group consisting of a pyrazole ring, an imidazole ring, a triazole ring, a tetrazole ring, a thiazole ring, a thiadiazole ring, an oxazole ring, and a pyrimidine ring.
[0021] [3] The adhesive composition according to [1] or [2], wherein:
[0022] The metal compound includes at least one selected from the group consisting of aluminum, magnesium, zirconium, bismuth, calcium, tin, manganese, antimony, and titanium.
[0023] [4] The adhesive composition according to any one of [1] to [3], wherein
[0024] The particles comprise a metal hydroxide.
[0025] [5] The adhesive composition according to any one of [1] to [4], wherein
[0026] The total content of the compound having a nitrogen-containing aromatic heterocyclic ring and the content of the particles is 0.1 parts by mass or more and 5 parts by mass or less relative to 100 parts by mass of the total amount of the radical polymerizable compound.
[0027] [6] The adhesive composition according to any one of [1] to [5], further comprising conductive particles.
[0028] [7] An adhesive film comprising an adhesive layer containing the adhesive composition according to any one of [1] to [6].
[0029] [8] A connection structure comprising:
[0030] A first circuit component having a first electrode;
[0031] a second circuit component having a second electrode; and
[0032] The connecting portion is disposed between the first circuit component and the second circuit component and electrically connects the first electrode and the second electrode to each other.
[0033] The connecting portion includes a cured product of the adhesive composition according to any one of [1] to [6].
[0034] [9] A method for manufacturing a connection structure, comprising the following steps:
[0035] The adhesive composition described in any one of [1] to [6] is interposed between a first circuit member having a first electrode and a second circuit member having a second electrode, and the first circuit member and the second circuit member are thermally compressed to electrically connect the first electrode and the second electrode to each other.
[0036] According to one aspect of the present invention, an adhesive composition capable of obtaining a connection structure having excellent salt water resistance is provided. In particular, in recent years, a higher degree of durability has been required, and salt water resistance under more severe conditions has been required year after year. According to the adhesive composition of the present invention, a connection structure that is not easily peeled off at the connection portion can be obtained even under more severe test conditions than those implemented in the past, such as under conditions of spraying salt water for a longer time.
[0037] Furthermore, according to one aspect of the present invention, it is possible to provide a connection structure having low connection resistance and capable of suppressing peeling at the interface between a circuit component and a connection portion when the connection structure is used in a high-temperature and high-humidity environment.
[0038] Effects of the Invention
[0039] According to the present invention, there can be provided an adhesive composition capable of obtaining a connection structure having excellent salt water resistance, an adhesive film using the adhesive composition, a connection structure, and a method for producing the same. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 It is a schematic cross-sectional view showing an adhesive film according to one embodiment.
[0041] Figure 2 It is a schematic cross-sectional view showing an adhesive film according to another embodiment.
[0042] Figure 3 It is a schematic cross-sectional view showing one embodiment of a connection structure. DETAILED DESCRIPTION
[0043] Hereinafter, embodiments of the present invention will be described in detail with reference to the drawings as appropriate. However, the present invention is not limited to the following embodiments.
[0044] In this specification, the numerical range represented by "~" indicates a range that includes the numerical values recorded before and after "~" as the minimum and maximum values, respectively. In the numerical range recorded in stages in this specification, the upper limit or lower limit of the numerical range of a certain stage can be replaced by the upper limit or lower limit of the numerical range of other stages. Moreover, in the numerical range recorded in this specification, the upper limit or lower limit of its numerical range can be replaced by the value shown in the embodiment. Moreover, the upper limit and lower limit of individual records can be combined arbitrarily. Moreover, in this specification, "(meth)acrylate" refers to at least one of acrylate and its corresponding methacrylate. Other similar expressions such as "(meth)acryloyl" are also the same. Moreover, "(poly)" refers to two cases where the prefix "poly" exists and does not exist. Moreover, with respect to "A or B", as long as any one of A and B is included, both can be included. Moreover, unless otherwise specified, the materials exemplified below can be used alone or in combination of two or more. When a plurality of substances corresponding to each component are present in the composition, the content of each component in the composition represents the total amount of the plurality of substances present in the composition unless otherwise specified.
[0045] <Adhesive composition>
[0046] The adhesive composition of the present embodiment contains a radical polymerizable compound (also referred to as a radical polymerizable substance or a radical reactive component), a radical polymerization initiator, a compound having a nitrogen-containing aromatic heterocyclic ring, and particles containing at least one metal compound selected from the group consisting of metal hydroxides and metal oxides.
[0047] [Radical polymerizable compound]
[0048] The free radical polymerizable compound is a compound having a functional group capable of free radical polymerization. Examples of such compounds include vinyl compounds having a vinyl group, (meth)acrylate compounds having a (meth)acryloyl group, and the like. The free radical polymerizable compound can be used in the form of a monomer or an oligomer, and a monomer and an oligomer can also be used in combination. The free radical polymerizable compound can be used alone or in combination of two or more.
[0049] From the viewpoint of obtaining more excellent salt water resistance, the radical polymerizable compound is preferably a (meth)acrylate compound. Examples of the (meth)acrylate compound include ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, tetramethylolmethane tetra(meth)acrylate, 2-hydroxy-1,3-di(meth)acryloyloxypropane, 2,2-bis[4-((meth)acryloyloxymethoxy)phenyl]propane, 2,2-bis[4-((meth)acryloyloxypolyethoxy)phenyl]propane, dicyclopentyl(meth)acrylate, tricyclodecyl(meth)acrylate, tri((meth)acryloyloxyethyl)isocyanurate, (poly)urethane(meth)acrylate, dimethyloltricyclodecane di(meth)acrylate, isocyanuric acid EO (ethylene oxide) modified diacrylate, and 2-methacryloyloxyethyl phosphate.
[0050] From the viewpoint of balancing the crosslinking density and the curing shrinkage, further reducing the connection resistance, and improving the reliability of the high temperature and high humidity connection, the (meth)acrylate compound may be a (poly)urethane (meth)acrylate. Based on the total mass of the free radical polymerizable compound, the content of the (poly)urethane (meth)acrylate may be 20% by mass or more, 40% by mass or more, or 60% by mass or more, and may be 90% by mass or less, or 80% by mass or less. The adhesive composition may contain only a (poly)urethane (meth)acrylate as a free radical polymerizable compound.
[0051] The weight average molecular weight of (poly)urethane (meth)acrylate can be 1.0×10 4 From the perspective of miscibility, it can be 1.0×10 4 Above and 1.0×10 6 The weight average molecular weight here was measured by gel permeation chromatography (GPC) under the conditions described in the Examples using a calibration curve based on standard polystyrene.
[0052] The (meth)acrylate compound can also use a compound having at least one partial structure selected from the group consisting of a dicyclopentane skeleton, a tricyclodecane skeleton and a triazine ring. By using a (meth)acrylate compound having such a partial structure as a free radical polymerizable compound, the cured product of the adhesive composition will have excellent heat resistance. From the perspective of balancing the crosslinking density and the shrinkage on cure, and further reducing the connection resistance, the (meth)acrylate compound can be a (meth)acrylate compound having a tricyclodecane skeleton. From the perspective of balancing the crosslinking density and the shrinkage on cure, the content of the (meth)acrylate compound having a tricyclodecane skeleton can be 1% by mass or more, 5% by mass or more, or 10% by mass or more, and can be 90% by mass or less, 60% by mass or less, or 30% by mass or less, based on the total mass of the free radical polymerizable compound.
[0053] The (meth)acrylate compound may be a compound represented by the following formula (1) (a (meth)acrylate compound having a phosphate structure). In this case, since the bonding strength to the surface of an inorganic substance (metal, etc.) is improved, the bonding between electrodes (for example, between circuit electrodes) is better.
[0054]
[0055] In formula (1), n represents an integer of 1 to 3, and R represents a hydrogen atom or a methyl group.
[0056] For example, a (meth)acrylate compound represented by formula (1) can be obtained by reacting phosphoric anhydride with 2-hydroxyethyl (meth)acrylate. Specific examples of the (meth)acrylate compound represented by formula (1) include mono(2-(meth)acryloyloxyethyl)phosphate and di(2-(meth)acryloyloxyethyl)phosphate.
[0057] From the viewpoint of reducing connection resistance and easily obtaining the cross-linking density required for improving connection reliability, the content of the (meth)acrylate compound represented by formula (1) can be 1% by mass or more, or 2% by mass or more, and can be 20% by mass or less, 10% by mass or less, or 5% by mass or less, based on the total mass of the free radical polymerizable compound.
[0058] As radical polymerizable compounds other than (meth)acrylate compounds, for example, compounds described in Patent Document 5 (International Publication No. 2009 / 063827) can be used.
[0059] The free radical polymerizable compound may be a polymer such as polyurethane, polystyrene, polyethylene, polyvinyl butyral, polyvinyl formal, polyimide, polyamide, polyester, polyvinyl chloride, polyphenylene oxiole, urea-formaldehyde resin, melamine resin, phenolic resin, xylene resin, epoxy resin, polyisocyanate resin, phenoxy resin, etc. These polymers have at least one free radical polymerizable functional group in the molecule.
[0060] If a polymer is used as a free radical polymerizable compound, the adhesive composition has excellent workability and excellent stress relaxation during curing. In addition, when the polymer has a functional group such as a hydroxyl group, the adhesiveness is also excellent. From this point of view, it is more preferred that each polymer is modified by a free radical polymerizable functional group.
[0061] The weight average molecular weight of the polymer can be 1.0×10 4 From the perspective of miscibility, it can be 1.0×10 4 Above and 1.0×10 6 The weight average molecular weight here was measured by gel permeation chromatography (GPC) under the conditions described in the Examples using a calibration curve based on standard polystyrene.
[0062] From the viewpoint of reducing connection resistance and easily obtaining the cross-linking density required for improving high temperature and high humidity resistant connection reliability, the content of the free radical polymerizable compound can be 5 mass % or more, 20 mass % or more, or 40 mass % or more, and can be 90 mass % or less, 75 mass % or less, or 60 mass % or less, based on the total mass of the resin component of the adhesive composition (components other than conductive particles and fillers (details will be described later). The same applies below).
[0063] [Free Radical Polymerization Initiator]
[0064] The radical polymerization initiator is a compound that generates free radicals, and for example, compounds that decompose and generate free radicals by heating, such as peroxide compounds and azo compounds, can be cited. The radical polymerization initiator can be appropriately selected according to the target connection temperature, connection time, etc. The radical polymerization initiator can be used alone or in combination of two or more.
[0065] Examples of the radical polymerization initiator include diacyl peroxides, peroxydicarbonates, peroxyesters, peroxyketals, dialkyl peroxides, and hydroperoxides.
[0066] Examples of the diacyl peroxides include bis(2,4-dichlorobenzoyl)peroxide, bis(3,5,5-trimethylhexanoyl)peroxide, octanoyl peroxide, lauroyl peroxide, stearoyl peroxide, succinic peroxide, benzoyl peroxytoluene, and benzoyl peroxide.
[0067] Examples of the peroxydicarbonates include di-n-propyl peroxydicarbonate, diisopropyl peroxydicarbonate, bis(4-tert-butylcyclohexyl)peroxydicarbonate, di-2-ethoxymethoxyperoxydicarbonate, di(2-ethylhexylperoxy)dicarbonate, dimethoxybutyl peroxydicarbonate, and di(3-methyl-3-methoxybutylperoxy)dicarbonate.
[0068] Examples of the peroxyesters include 1,1,3,3-tetramethylbutyl peroxyneodecanoate, 1-cyclohexyl-1-methylethyl peroxyneodecanoate, tert-hexyl peroxyneodecanoate, tert-butyl peroxytivalate, 1,1,3,3-tetramethylbutyl peroxy-2-ethylhexanoate, 2,5-dimethyl-2,5-bis(2-ethylhexanoylperoxy)hexane, 1-cyclohexyl-1-methylethyl peroxy-2-ethylhexanoate, tert-hexyl peroxy-2-ethylhexanoate, and tert-hexyl peroxy-2-ethylhexanoate. tert-Butyl peroxy-2-ethylhexanoate, tert-butyl peroxyisobutyrate, 1,1-bis(tert-butylperoxy)cyclohexane, tert-hexyl peroxyisopropyl monocarbonate, tert-butyl peroxy-3,5,5-trimethylacetate, tert-butyl peroxylaurate, 2,5-dimethyl-2,5-di(m-toluoylperoxy)hexane, tert-butyl peroxyisopropyl monocarbonate, tert-butyl peroxy-2-ethylhexyl monocarbonate, tert-hexyl peroxybenzoate, tert-butyl peroxyacetate, etc.
[0069] Examples of the peroxyketals include 1,1-bis(tert-hexylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-hexylperoxy)cyclohexane, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-(tert-butylperoxy)cyclododecane, and 2,2-bis(tert-butylperoxy)decane.
[0070] Examples of the dialkyl peroxides include α,α′-bis(tert-butylperoxy)diisopropylbenzene, diisopropylbenzene peroxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, and tert-butylisopropylbenzene peroxide.
[0071] Examples of the hydrogen peroxides include diisopropylbenzene hydroperoxide and cumene hydroperoxide.
[0072] These radical polymerization initiators may be used in combination with a decomposition accelerator, an inhibitor, etc. Furthermore, those obtained by coating these radical polymerization initiators with polyurethane-based or polyester-based polymers and forming microcapsules are preferred because they can extend the shelf life.
[0073] From the viewpoint of pot life, the content of the radical polymerization initiator may be 0.1 mass % or more, 0.5 mass % or more, or 1 mass % or more, and may be 20 mass % or less, 10 mass % or less, or 5 mass % or less, based on the total mass of the resin component of the adhesive composition.
[0074] [Compounds having a nitrogen-containing aromatic heterocyclic ring]
[0075] A compound having a nitrogen-containing aromatic heterocycle is a compound having an aromatic heterocycle containing one or more nitrogen atoms in the ring. The nitrogen-containing aromatic heterocycle is composed of at least two types of atoms, carbon atoms and nitrogen atoms, and may also be composed of three or more atoms including other atoms such as sulfur atoms and oxygen atoms in addition to carbon atoms and nitrogen atoms. The nitrogen-containing aromatic heterocycle contains, for example, 1 to 4 nitrogen atoms, preferably 2 to 4 nitrogen atoms. When the nitrogen atom contained in the nitrogen-containing aromatic heterocycle is 1, the nitrogen-containing aromatic heterocycle preferably contains the above-mentioned other atoms in addition to carbon atoms and nitrogen atoms.
[0076] The nitrogen-containing aromatic heterocycle is preferably a compound having a 5-membered ring or a 6-membered ring, and more preferably a compound having a 5-membered ring (azole). As the 5-membered ring, for example, a pyrazole ring, an imidazole ring, a triazole ring, a tetrazole ring, a thiazole ring, a thiadiazole ring, an oxazole ring, etc. can be cited. As the 6-membered ring, for example, a pyrimidine ring, etc. can be cited.
[0077] From the viewpoint of suppressing the increase in connection resistance and further improving the connection reliability, the nitrogen-containing aromatic heterocycle is preferably at least one selected from the group consisting of a pyrazole ring, an imidazole ring, a triazole ring, a tetrazole ring, a thiazole ring, a thiadiazole ring, an oxazole ring and a pyrimidine ring, more preferably at least one selected from the group consisting of a pyrazole ring, an imidazole ring, a triazole ring, a tetrazole ring, a thiazole ring, a thiadiazole ring and an oxazole ring, and further preferably at least one selected from the group consisting of a triazole ring, a tetrazole ring and a thiadiazole ring.
[0078] The nitrogen-containing aromatic heterocycle may be unsubstituted or may have a substituent (the hydrogen atom bonded to the atom constituting the nitrogen-containing aromatic heterocycle is substituted). When the nitrogen-containing aromatic heterocycle has a substituent, the substituent may be a hydrocarbon group or an organic group containing a sulfur atom, an oxygen atom, etc. The hydrocarbon group may be an alkyl group, etc. The organic group containing a nitrogen atom may be an amino group, etc. The organic group containing a sulfur atom may be a mercapto group, etc.
[0079] The compound having a nitrogen-containing aromatic heterocycle may have a nitrogen-containing aromatic heterocycle composed of a single ring, for example, or may have a polycyclic ring formed by condensation of an aromatic ring composed only of hydrocarbons (for example, a substituted or unsubstituted benzene ring) and the above-mentioned nitrogen-containing aromatic heterocycle. Such a polycyclic ring may be, for example, a benzimidazole ring, a benzotriazole ring, a benzothiazole ring, a benzoxazole ring, etc.
[0080] Regarding the compound having a nitrogen-containing aromatic heterocyclic ring, more specifically, it can be 1H-1,2,4-triazole, 3-amino-1H-1,2,4-triazole, 3-mercapto-1,2,4-triazole, 1H-tetrazole, 5-methyl-1H-tetrazole, 5-amino-1H-tetrazole, 2-amino-5-mercapto-1,3,4-thiadiazole, 2-aminopyrimidine, 2-mercaptopyrimidine, 5,6-dimethylbenzimidazole, 2-mercaptobenzimidazole, benzotriazole, 2-mercaptobenzothiazole, 2-mercaptobenzoxazole, etc.
[0081] From the viewpoint of obtaining better salt water resistance, the content of the compound having a nitrogen-containing aromatic heterocyclic ring can be 0.1 mass % or more, 0.25 mass % or more, or 0.5 mass % or more, and can be 5 mass % or less, 3 mass % or less, or 1 mass % or less, based on the total mass of the resin component of the adhesive composition.
[0082] From the viewpoint of obtaining better salt water resistance, the content of the compound having a nitrogen-containing aromatic heterocycle can be 0.1 parts by mass or more, 0.5 parts by mass or more, 1 part by mass or more, or 3 parts by mass or more, and can be 5 parts by mass or less, 3 parts by mass or less, or 1 part by mass or less, relative to 100 parts by mass of the total amount of the radical polymerizable compound.
[0083] [Particles containing metal compounds]
[0084] The adhesive composition contains particles containing at least one metal compound selected from the group consisting of metal hydroxides and metal oxides. The particles are particles of a different type from the conductive particles described below. The particles may contain metal hydroxides or metal oxides.
[0085] However, one of the reasons why the connection structure connected by the adhesive composition of the previous free radical curing system is prone to peeling of the connection part in the salt water spray test is that the polarity of the cured product of the adhesive composition that becomes the connection part is low. For example, when the polymer of the free radical polymerizable compound has a carbon-carbon bond (CC) as the main skeleton, there is a tendency for low polarity. It is believed that in this case, the adhesion of the interface between the adherend (substrate, etc.) and the cured product of the adhesive composition is insufficient, and the ionic components in the salt water easily invade the interface, thereby causing adhesion obstruction. In particular, when the adherend has a SiO2, SiN xWhen the insulating material part of an insulating material such as an insulating material is connected to an insulating material, since the insulating material part has multiple hydroxyl groups on the surface and is easily wetted by water (salt water, etc.), but is not easily wetted by the adhesive composition of the free radical curing system, it is easy to cause adhesion obstruction. In contrast, in the adhesive composition of the present embodiment, by including metal oxides and / or metal hydroxides, the polarity of the adhesive composition itself is improved, and the ionic components that cause adhesion obstruction are captured by the metal oxides and / or metal hydroxides, and the adhesion obstruction is suppressed, thereby improving the salt water resistance of the connected structure. In addition, in the adhesive composition of the present embodiment, in addition to this specific metal compound, a compound having a nitrogen-containing aromatic heterocycle is also used, thereby, even under the condition of spraying salt water for a longer time, the peeling of the connection part can be suppressed.
[0086] The metal compound may contain at least one selected from the group consisting of aluminum, magnesium, zirconium, bismuth, calcium, tin, manganese, antimony, titanium and silicon as a metal element constituting the metal hydroxide or the metal oxide. The metal compound may be a metal compound containing a trivalent or tetravalent metal.
[0087] As metal hydroxides, aluminum hydroxide, magnesium hydroxide, calcium hydroxide, magnesium aluminum hydrotalcite, etc. can be mentioned. As metal oxides, aluminum oxide, magnesium oxide, antimony oxide, tin oxide, titanium oxide, manganese oxide, zirconium oxide, silicon oxide, etc. can be mentioned. The particles containing metal compounds can use these compounds alone or in combination of two or more. It is also possible to use particles containing metal hydroxides and particles containing metal oxides in combination.
[0088] With respect to the viewpoints of obtaining excellent dispersibility in the adhesive composition and high adhesion to the adherend, preventing corrosion of the adherend, obtaining the ability to capture ion components, and suppressing short circuits caused by large particles (short circuits when particles containing metal compounds become foreign matter), the average primary particle size of particles containing metal compounds can be less than 10 μm, less than 5 μm, or less than 1 μm. It is believed that by reducing the average primary particle size of particles containing metal compounds, the specific surface area of the entire particle in the adhesive composition increases, thereby obtaining the effect of high adhesion to the adherend, preventing corrosion of the adherend, and obtaining the effect of capturing ion components. The average primary particle size of particles containing metal compounds can be more than 0.5 μm, or more than 1 μm. The average primary particle size of particles containing metal compounds can be measured, for example, by a scanning electron microscope.
[0089] The content of the particles containing the metal compound may be 0.1 mass % or more, 0.25 mass % or more, or 0.5 mass % or more, and 5 mass % or less, 3 mass % or less, or 1 mass % or less, based on the total mass of the resin component of the adhesive composition.
[0090] The content of particles containing metal compounds can be 0.1 mass parts or more, 0.5 mass parts or more, 1 mass parts or more, 2 mass parts or more, or 3 mass parts or more, relative to 100 mass parts of the total amount of free radical polymerizable compounds, and can be 7 mass parts or less, 5 mass parts or less, 3 mass parts or less, or 1 mass part or less.
[0091] From the viewpoint of obtaining better salt water resistance, the total amount of the above-mentioned compound having a nitrogen-containing aromatic heterocycle and the content of particles containing a metal compound can be 0.1 mass parts or more, 0.5 mass parts or more, or 3 mass parts or more, and can be 5 mass parts or less, 3 mass parts or less, or 1 mass part or less, relative to 100 mass parts of the total amount of the free radical polymerizable compound.
[0092] [Thermoplastic resin]
[0093] The adhesive composition may contain a thermoplastic resin. If the adhesive composition contains a thermoplastic resin, the handling can be facilitated when the adhesive composition is formed into a film.
[0094] As the thermoplastic resin, polyvinyl butyral resin, polyvinyl formal resin, polyamide resin, polyester resin, phenol resin, epoxy resin, phenoxy resin, polystyrene resin, xylene resin, polyurethane resin, polyester urethane resin, etc. can be used. These can be used alone or in combination of two or more.
[0095] From the viewpoint of achieving excellent film-forming properties of the adhesive composition, the weight average molecular weight of the thermoplastic resin may be 1.0×10 4 From the perspective of miscibility, it can be 1.0×10 4 More than and less than 1.0×10 6 The weight average molecular weight here is measured by gel permeation chromatography (GPC) under the conditions described in the Examples using a calibration curve based on standard polystyrene.
[0096] As the thermoplastic resin, a thermoplastic resin having a Tg (glass transition temperature) of 40° C. or higher and a weight average molecular weight of 1.0×10 4 The above hydroxyl group-containing resin (eg, phenoxy resin) may be modified with an epoxy group-containing elastomer.
[0097] The phenoxy resin can be obtained by reacting a difunctional phenol with epichlorohydrin to a high molecular weight or by subjecting a difunctional epoxy resin to a polyaddition reaction with a difunctional phenol.
[0098] As the thermoplastic resin, polyester urethane resin can be used.
[0099] In the present specification, a thermoplastic resin having a radical polymerizable functional group is blended as the radical polymerizable compound.
[0100] The content of the thermoplastic resin may be 5% by mass or more or 30% by mass or more and 80% by mass or less or 60% by mass or less, based on the total mass of the resin components of the adhesive composition.
[0101] [Conductive particles]
[0102] The adhesive composition may contain conductive particles. The conductive particles may be metal particles such as Au, Ag, Ni, Cu, solder, conductive carbon particles composed of conductive carbon, etc. The conductive particles may be particles formed by coating the surface of transition metals such as Ni with precious metals such as Au. From the perspective of obtaining a sufficient shelf life, the surface layer can be Au, Ag, platinum group precious metals, or Au. The conductive particles may be coated conductive particles in which a conductive layer is formed on the surface of non-conductive particles by coating the surface of non-conductive particles such as glass, ceramics, plastics, etc. with the above-mentioned conductive material, and the outermost layer is composed of precious metals. When such particles or hot-melt metal particles are used, they are deformable by heating and pressurizing, so the contact area with the electrode is increased during connection, thereby improving reliability.
[0103] The conductive particles may be the above-mentioned metal particles, conductive carbon particles, or coated conductive particles and insulating coated conductive particles, wherein the insulating coated conductive particles contain an insulating material such as a resin and have an insulating layer covering the surface of the particles. If the conductive particles are insulating coated conductive particles, even when the content of the conductive particles is high, since the surface of the particles is coated with resin, short circuits caused by contact between the conductive particles can be suppressed, and the insulation between adjacent electrode circuits can be improved.
[0104] Regarding the conductive particles, the above-mentioned various conductive particles may be used alone or in combination of two or more.
[0105] The maximum particle size of the conductive particles needs to be smaller than the minimum spacing of the electrodes (the shortest distance between adjacent electrodes). From the perspective of excellent dispersibility and conductivity, the maximum particle size of the conductive particles can be more than 1.0 μm, more than 2.0 μm or more than 2.5 μm. From the perspective of excellent dispersibility and conductivity, the maximum particle size of the conductive particles can be less than 50 μm, less than 30 μm or less than 20 μm. In this specification, for any 300 (pcs) conductive particles, the particle size is measured by observation using a scanning electron microscope (SEM), and the maximum value obtained is used as the maximum particle size of the conductive particles. In addition, when the conductive particles have protrusions and are not spherical, the particle size of the conductive particles is set to the diameter of the circumscribed circle of the conductive particles in the SEM image.
[0106] From the viewpoint of excellent dispersibility and conductivity, the average particle size of the conductive particles can be 1.0 μm or more, 2.0 μm or more, or 2.5 μm or more. From the viewpoint of excellent dispersibility and conductivity, the average particle size of the conductive particles can be 50 μm or less, 30 μm or less, or 20 μm or less. In this specification, for any 300 (pcs) conductive particles, the particle size is measured by observation using a scanning electron microscope (SEM), and the average value of the obtained particle size is taken as the average particle size.
[0107] In order to easily obtain stable connection resistance, the content of the conductive particles may be in the range of 0.1 to 30 parts by volume relative to 100 parts by volume of the resin component of the adhesive composition. In order to prevent short circuits of adjacent circuits caused by excessive conductive particles, the content of the conductive particles may be in the range of 0.1 to 10 parts by volume.
[0108] From the perspective of easily obtaining stable connection resistance, the content of the conductive particles can be 0.5 to 60 mass %, 3 to 45 mass % or 6 to 30 mass % based on the total mass of the radical polymerizable compound, the radical polymerization initiator, the compound having a nitrogen-containing aromatic heterocycle, the particles containing the metal compound and the thermoplastic resin in the adhesive composition.
[0109] [Other ingredients]
[0110] The adhesive composition may contain other components in addition to the above components. Examples of other components include thiol compounds, coupling agents, fillers, etc. These components may be used alone or in combination of two or more.
[0111] The thiol compound may be a thiol compound having one thiol group (monofunctional thiol compound) or a thiol compound having a plurality of thiol groups (polyfunctional thiol compound).
[0112] The thiol group of the thiol compound may be a primary thiol group, a secondary thiol group, or a tertiary thiol group.
[0113] Examples of the monofunctional thiol compound include 2-mercaptobenzothiazole, 2-methyl-4,5-dihydrofuran-3-thiol, 3-mercapto-1-hexanol, mercaptomethylbutanol, 3-mercapto-2-methylpentanol, 3-mercapto-3-methylbutanol, 4-ethoxy-2-methyl-2-butanethiol, hexanethiol, isobutyl mercaptan, 1,1-dimethylheptylthiol, 2-ethylhexyl-3-mercaptopropionate, n-octyl-3-mercaptopropionate, methoxybutyl-3-mercaptopropionate, and stearyl-3-mercaptopropionate.
[0114] Examples of the polyfunctional thiol compound include pentaerythritol tetrakis(3-mercaptobutyrate), ethanedithiol, 1,3-propanethiol, 1,4-butanethiol, trimethylolpropane tris(3-mercaptopropionate), tris-[(3-mercaptopropionyloxy)-ethyl]-isocyanurate, and tetraethylene glycol bis(3-mercaptopropionate).
[0115] From the viewpoint of suppressing peeling at the interface between the cured adhesive composition and the circuit component and suppressing the increase in the connection resistance of the circuit connection structure, the content of the thiol compound can be 0.05 mass% or more, 0.5 mass% or more, 1.0 mass% or more, or 1.5 mass% or more, based on the total mass of the resin component of the adhesive composition. From the viewpoint of suppressing peeling at the interface between the cured adhesive composition and the circuit component and suppressing the increase in the connection resistance of the circuit connection structure, it can be 5.0 mass% or less, 3.0 mass% or less, 2.5 mass% or less, or 2.0 mass% or less.
[0116] As the coupling agent, from the viewpoint of improving adhesion, a compound having at least one of a vinyl group, an acryl group, an amino group, an epoxy group, and an isocyanate group can be used.
[0117] As the filling material, for example, non-conductive fillers (for example, non-conductive particles) can be cited. The filling material can be any of an inorganic filler and an organic filler. As the inorganic filler, for example, metal oxide particles such as silica particles, alumina particles, silica-alumina particles, titanium dioxide particles, and zirconium oxide particles; inorganic particles such as nitride particles can be cited. As the organic filler, for example, organic particles such as silicone particles, methacrylate-butadiene-styrene particles, acrylic-silicone particles, polyamide particles, and polyimide particles can be cited. These particles can have a uniform structure or a core-shell structure. The maximum diameter of the filling material can be smaller than the minimum particle size of the conductive particles.
[0118] The content of the filler may be 4 to 60% by volume, 5 to 50% by volume, or 6 to 30% by volume based on the total volume of the adhesive composition. From the perspective of improving connection reliability, the content of the filler may be 3 to 60% by mass, 4 to 40% by mass, or 5 to 20% by mass based on the total mass of the free radical polymerizable compound, free radical polymerization initiator, compound having a nitrogen-containing aromatic heterocycle, particles containing a metal compound, and thermoplastic resin in the adhesive composition.
[0119] The adhesive composition may further contain other additives such as a softener, an accelerator, an anti-aging agent, a colorant, a flame retardant, a thixotropic agent, a polymerization inhibitor, etc. Examples of the polymerization inhibitor include hydroquinone and hydroquinone methyl ether.
[0120] The adhesive composition described above is suitably used as a circuit-connecting adhesive composition for connecting circuit components having electrodes with the electrodes facing each other, and is particularly suitably used as an anisotropic conductive adhesive composition for connecting circuit components.
[0121] <Adhesive film>
[0122] From the viewpoint of workability, the above-mentioned adhesive composition can be used as an adhesive film formed into a film shape. Figure 1 It is a schematic cross-sectional view showing an adhesive film according to one embodiment. Figure 1 The adhesive film 1A shown has an adhesive layer 2 containing the above-mentioned adhesive composition. The adhesive layer 2 contains an adhesive component (components other than the conductive particles in the adhesive composition) 3 and conductive particles 4 dispersed in the adhesive component 3. The thickness of the adhesive film 1A may be 10 μm or more, or 50 μm or less.
[0123] In another embodiment, the adhesive film may include a plurality of adhesive layers. If the adhesive film including a plurality of adhesive layers is used for connecting circuit components, stable connection resistance can be easily obtained. Figure 2 It is a schematic cross-sectional view of an adhesive film according to another embodiment. Figure 2 The adhesive film 1B shown includes a first adhesive layer 5 and a second adhesive layer 6 laminated on the first adhesive layer 5 .
[0124] The first adhesive layer 5 contains the above-mentioned adhesive composition. That is, the first adhesive layer 5 contains the adhesive component 3 and the conductive particles 4 dispersed in the adhesive component 3.
[0125] The second adhesive layer 6 contains, for example, a radical polymerizable compound and a radical polymerization initiator. As the radical polymerization initiator and the radical polymerization initiator, the radical polymerization initiator and the radical polymerization initiator used in the above-mentioned adhesive composition can be used. The second adhesive layer 6 may further contain the components exemplified as other components in the above-mentioned thermoplastic resin and the adhesive composition. The second adhesive layer 6 may not contain conductive particles.
[0126] The thickness of the first adhesive layer 5 and the second adhesive layer 6 can be appropriately set according to the height of the electrode of the circuit component to be bonded, etc. The thickness of the first adhesive layer 5 can be, for example, 0.5 μm or more and can be 20 μm or less. The thickness of the second adhesive layer 6 can be, for example, 5 μm or more and can be 200 μm or less. The thickness of the adhesive film 1B (the total thickness of the first adhesive layer 5 and the second adhesive layer 6) can be, for example, 5 μm or more and can be 200 μm or less.
[0127] The adhesive film is not limited to the above-mentioned embodiment, and may be, for example, an adhesive film having an adhesive layer containing no conductive particles. The adhesive film may be a three-layer film consisting of an adhesive layer containing conductive particles and adhesive layers containing no conductive particles disposed on both sides thereof.
[0128] The adhesive film can be suitably used as an adhesive film for circuit connection for connecting circuit components having electrodes with the electrodes being arranged to face each other.
[0129] The adhesive film of the present embodiment can be produced by the following method. Specifically, first, each component (e.g., adhesive component and conductive particles) included in the adhesive layer is added to a solvent such as an organic solvent, and dissolved or dispersed by stirring, mixing, kneading, etc. to prepare a varnish composition (varnish-like adhesive composition). Then, the varnish composition is applied to a substrate subjected to a demolding treatment using a knife coater, a roll coater, an applicator, a comma coater, a die coater, etc., and the solvent is volatilized by heating, thereby forming an adhesive film on the substrate.
[0130] As the solvent for preparing the varnish composition, a solvent having the characteristic of being able to uniformly dissolve or disperse each component can be used. As such a solvent, for example, toluene, acetone, methyl ethyl ketone, methyl isobutyl ketone, ethyl acetate, propyl acetate, butyl acetate, etc. can be cited. These solvents can be used alone or in combination of two or more. The stirring, mixing and mixing when preparing the varnish composition can be carried out using, for example, a stirrer, a crushing machine, a three-roller machine, a ball mill, a bead mill, a homogenizing disperser.
[0131] The substrate is not particularly limited as long as it is a material with heat resistance that can withstand the heating conditions during volatilization of the solvent. For example, films formed from stretched polypropylene (OPP), polyethylene terephthalate (PET), polyethylene naphthalate, polyethylene isophthalate, polybutylene terephthalate, polyolefins, polyacetate, polycarbonate, polyphenylene sulfide, polyamide, polyimide, cellulose, ethylene-vinyl acetate copolymer, polyvinyl chloride, polyvinylidene chloride, synthetic rubbers, liquid crystal polymers, etc. can be used.
[0132] The heating conditions for volatilizing the solvent from the varnish composition applied to the substrate can be set to conditions that allow the solvent to fully volatilize. The heating conditions can be, for example, 40° C. to 120° C. and 0.1 minute to 10 minutes.
[0133] The adhesive film of this embodiment may not remove part of the solvent and may remain. For example, the content of the solvent in the adhesive film for circuit connection of this embodiment may be 10% by mass or less, or 5% by mass or less, based on the total mass of the adhesive film.
[0134] <Circuit connection structure and method for manufacturing the same>
[0135] Next, the circuit connection structure and its manufacturing method are described.
[0136] The connection structure of this embodiment includes: a first circuit component having a first electrode; a second circuit component having a second electrode; and a connection portion, which is arranged between the first circuit component and the second circuit component and electrically connects the first electrode and the second electrode to each other, and the connection portion includes a cured product of the adhesive composition of this embodiment.
[0137] Figure 3 It is a schematic cross-sectional view showing one embodiment of a connection structure. Figure 3 The connection structure 10 shown comprises: a first circuit component 13 having a first substrate 11 and a first electrode (first connection terminal) 12 formed on a main surface 11a thereof; a second circuit component 16 having a second substrate 14 and a second electrode (second connection terminal) 15 formed on a main surface 14a thereof; and a connection portion 17 interposed between the first circuit component 13 and the second circuit component 16 to bond them together. The second circuit component 16 is disposed opposite to the first circuit component 13 in such a manner that the second electrode 15 and the first electrode 12 are opposite to each other.
[0138] The connection portion 17 includes a cured product of the adhesive composition, and is composed of a cured product 18 of the adhesive component and conductive particles 4 dispersed in the cured product 18. The opposing first electrode 12 and second electrode 15 are electrically connected via the conductive particles 4. On the other hand, the first electrodes 12 and the second electrodes 15 formed on the same substrate are insulated from each other.
[0139] As the first substrate 11 and the second substrate 14, chip components such as semiconductor chips, resistor chips, capacitor chips, and substrates such as printed circuit boards can be cited. Usually, a large number of connection terminals are provided on the circuit components, but the number of connection terminals can be singular depending on the situation. More specifically, a substrate made of inorganic materials such as semiconductors, glass and ceramics, a plastic substrate or a glass / epoxy substrate is used. As the plastic substrate, polyimide film, polycarbonate film and polyester film can be cited.
[0140] The first electrode 12 and the second electrode 15 are formed of a metal such as copper. In order to obtain a better electrical connection, it is preferred to form a surface layer containing a metal selected from gold, silver, tin and platinum group on at least one of the first electrode 12 and the second electrode 15. The surface layer is selected from any one of gold, silver, platinum group or tin, and they may be used in combination. In addition, a plurality of metals may be combined to form a multilayer structure such as copper / nickel / gold.
[0141] One of the first circuit component 13 and the second circuit component 16 may be a liquid crystal display panel having a glass substrate or a plastic substrate as a circuit substrate and having connection terminals formed of ITO or the like. Furthermore, one of the first circuit component 13 and the second circuit component 16 may be a flexible printed circuit board (FPC), a tape carrier package (TCP) or a chip on film (COF) having a polyimide film as a circuit substrate, or a semiconductor silicon chip having a semiconductor substrate as a circuit substrate. These various circuit components are appropriately combined as needed to form a circuit connection structure.
[0142] In addition, in order to eliminate the influence of volatile components due to heating during connection on the connection, the substrate provided with electrodes is preferably subjected to a heat treatment before connection using the adhesive composition.
[0143] The method for manufacturing the connection structure involved in this embodiment includes the following steps: placing the adhesive composition of this embodiment between a first circuit component having a first electrode and a second circuit component having a second electrode, and thermally pressing the first circuit component and the second circuit component to electrically connect the first electrode and the second electrode to each other.
[0144] Specifically, first, a first circuit component 13 having a first substrate 11 and a first electrode (first connecting terminal) 12 formed on its main surface 11a and a second circuit component 16 having a second substrate 14 and a second electrode (second connecting terminal) 15 formed on its main surface 14a are prepared. Then, the first circuit component 13 and the second circuit component 16 are arranged in a manner that the first electrode 12 and the second electrode 15 are opposed to each other, and an adhesive composition is arranged between the first circuit component 13 and the second circuit component 16.
[0145] Regarding the adhesive composition disposed between the first circuit component 13 and the second circuit component 16, the above-mentioned adhesive film 1A or 1B may be disposed, or a varnish composition (varnish-like adhesive composition) may be applied to the first circuit component 13 or the second circuit component 16 or both.
[0146] When using an adhesive film 1B having two adhesive layers, the adhesive film 1B can be configured so that the first adhesive layer 5 side containing conductive particles is opposite to the first circuit component 13, and the second adhesive layer 6 side not containing conductive particles is opposite to the second circuit component 16. Alternatively, the adhesive film 1B can be configured so that the first adhesive layer 5 side is opposite to the second circuit component 16, and the second adhesive layer 6 side is opposite to the first circuit component 13.
[0147] Next, the first circuit component 13 and the second circuit component 16 are pressed in the thickness direction while heating the first circuit component 13, the adhesive film 1A, and the second circuit component 16, thereby thermally pressing the first circuit component 13 and the second circuit component 16. The adhesive component of the adhesive composition is cured by heating, and as a result, the first circuit component 13 and the second circuit component 16 are pressed together via the cured product of the adhesive composition.
[0148] The pressure during pressurization is not particularly limited as long as it does not damage the adherend, and is usually preferably 0.1 to 10 MPa. The heating temperature is not particularly limited, and is preferably 100 to 200° C. These pressurization and heating are preferably carried out in the range of 0.5 seconds to 100 seconds, and even heating for 10 seconds at 130 to 180° C. and 3 MPa can also make it adhere.
[0149] Example
[0150] Hereinafter, the present invention will be described in more detail with reference to Examples, but the present invention is not limited to these Examples.
[0151] <Synthesis of polymerizable compound (urethane acrylate (UA1))>
[0152] 2500 parts by mass (2.50 mol) of poly (1,6-hexanediol carbonate) (product name: DURANOL T5652, manufactured by ASAHI KASEI CORPORATION, number average molecular weight 1000) and 666 parts by mass (3.00 mol) of isophorone diisocyanate (manufactured by Sigma Aldrich) were uniformly added dropwise over 3 hours to a reaction vessel equipped with a stirrer, a thermometer, a reflux cooling tube with a calcium chloride drying tube, and a nitrogen introduction tube. Then, after nitrogen was fully introduced into the reaction vessel, the reaction vessel was heated to 70-75° C. to react. Next, 0.53 parts by mass (4.3 mmol) of hydroquinone monomethyl ether (manufactured by Sigma Aldrich) and 5.53 parts by mass (8.8 mmol) of dibutyltin dilaurate (manufactured by Sigma Aldrich) were added to the reaction container, and then 238 parts by mass (2.05 mol) of 2-hydroxyethyl acrylate (manufactured by Sigma Aldrich) was added, and the mixture was reacted for 6 hours at 70° C. under an air atmosphere. Thus, polyurethane acrylate (UA1) was obtained. The weight average molecular weight of polyurethane acrylate (UA1) was 15,000. In addition, the weight average molecular weight was measured by gel permeation chromatography (GPC) using a calibration curve based on standard polystyrene under the following conditions.
[0153] (Measurement conditions)
[0154] Equipment used: GPC-8020 manufactured by Tosoh Corporation
[0155] Detector: RI-8020 manufactured by Tosoh Corporation
[0156] Chromatographic column: Gelpack GLA160S+GLA150S manufactured by Hitachi Chemical Company, Ltd.
[0157] Sample concentration: 120mg / 3mL
[0158] Solvent: Tetrahydrofuran
[0159] Injection volume: 60μL
[0160] Pressure: 2.94×10 6 Pa(30kgf / cm 2 )
[0161] Flow rate: 1.00mL / min
[0162] <Production of Conductive Particles>
[0163] A layer made of nickel was formed on the surface of the polystyrene particles so that the thickness of the layer was 0.2 μm. In this way, conductive particles having an average particle size of 4 μm, a maximum particle size of 4.5 μm, and a specific gravity of 2.5 were obtained.
[0164] <Preparation of Adhesive Films (Examples 1 to 6, Comparative Examples 1 to 12)>
[0165] The components shown below were mixed in the blending amounts (unit: parts by mass) shown in Tables 1 to 3 to prepare varnish compositions (varnish-like adhesive compositions).
[0166] [Thermoplastic resin]
[0167] A1: A 40 mass % solution prepared by dissolving 40 g of bisphenol A type phenoxy resin (product name: PKHC, manufactured by UNION CARBIDE JAPAN LIMITED.) in 60 g of methyl ethyl ketone (the blending amount in the table indicates the blending amount of bisphenol A type phenoxy resin)
[0168] [Radical polymerizable compound]
[0169] B1: Polyurethane acrylate (UA1) synthesized as described above
[0170] B2: diacrylate having a tricyclodecane skeleton (dicyclopentadiene type diacrylate) (product name: DCP-A, manufactured by KYOEISHA CHEMICAL CO., LTD.)
[0171] B3: 2-methacryloyloxyethyl phosphate (product name: LIGHT ESTER P-2M, manufactured by KYOEISHA CHEMICAL Co., LTD.)
[0172] [Free Radical Polymerization Initiator]
[0173] C1: Benzoyl peroxide (product name: NYPER BMT-K40, manufactured by NOF CORPORATION)
[0174] [Compounds having a nitrogen-containing aromatic heterocyclic ring]
[0175] D1: 5-Methyl-1H-tetrazolyl
[0176] D2: 3-Mercapto-1,2,4-triazole
[0177] D3: Benzotriazole
[0178] [Metal compounds other than conductive particles]
[0179] E1: Zirconium oxide (ZrO2)
[0180] E2: Aluminum hydroxide (Al(OH)3)
[0181] [Other ingredients]
[0182] F1: Conductive particles obtained by the above process
[0183] G1: thiol compound (pentaerythritol tetrakis(3-mercaptobutyrate), product name: Karenz MT PE-1 ("Karenz MT" is a registered trademark), manufactured by Showa Denko KK), viscosity (@25°C): 1 Pa·s, molecular weight: 544.8)
[0184] H1: coupling agent (3-methacryloxypropyltrimethoxysilane (product name: KBM503, manufactured by Shin-Etsu Chemical Co., Ltd.)
[0185] I1: Filler (silicon dioxide fine particles (product name: R104, manufactured by NIPPON AEROSIL CO., LTD., average particle size (primary particle size): 12 nm))
[0186] The varnish composition was applied onto a substrate (PET film) having a thickness of 50 μm using a coating device. Then, hot air drying was performed at 70° C. for 3 minutes to form an adhesive layer on the substrate to produce an adhesive film. The thickness of the adhesive layer (thickness after drying) was 10 μm.
[0187] <Production of connection structure>
[0188] Through the prepared adhesive film, COF (manufactured by FLEXSEED) with a pitch of 25 μm and a thin film electrode (height: ) was connected across a width of 1 mm by heating and pressing a glass substrate with a thin film electrode (manufactured by DIOMATEC CO., LTD.) using a thermocompression bonding device (heating method: constant heat type, manufactured by TAIYO KIKAI LTD.) at 180° C. and 4.5 MPa for 4 seconds. Thus, a connection structure (circuit connection structure) in which the COF and the glass substrate with a thin film electrode were connected via the cured product of the above-mentioned adhesive composition was obtained.
[0189] <Evaluation of salt water resistance>
[0190] The connection structure was subjected to a 24-hour and 96-hour salt spray test according to JIS Z 2371 using a salt spray tester (manufactured by Suga Test Instruments Co., Ltd.). The appearance of the connection portion (cured product of the adhesive composition) in the connection structure before and after the test was observed by an optical microscope. From the glass substrate side with a thin film electrode, it was visually confirmed whether peeling occurred at the interface between the glass substrate and the connection portion. If peeling occurred, the peeling area was calculated and evaluated in 5 stages according to the following criteria. The results are shown in Tables 1 to 3.
[0191] S: The ratio of peeling area is less than 5%
[0192] A: The ratio of the peeling area is 5% or more and less than 10%
[0193] B: The ratio of the peeling area is 10% or more and less than 30%
[0194] C: The ratio of the peeling area is 30% or more and less than 60%
[0195] D: The ratio of peeling area is 60% or more [Table 1]
[0196]
[0197] [Table 2]
[0198]
[0199] [Table 3]
[0200]
[0201] <Evaluation of connection structures immediately after connection and after high temperature and high humidity testing>
[0202] The connection resistance, adhesion and peeling area of the connection structure involved in the embodiment were evaluated by the following method immediately after connection and after the high temperature and high humidity test. The high temperature and high humidity test was performed by placing the connection structure in a constant temperature and humidity chamber at 85°C and 85%RH for 100 hours. The results are shown in Table 4.
[0203] [Connection resistance]
[0204] The connection resistance between the electrodes facing each other in the connection structure was measured with a multimeter. The average value of the resistance between the electrodes facing each other at 16 points was obtained as the connection resistance value, and the connection resistance was evaluated in four levels according to the following criteria.
[0205] A: 3.0Ω or less
[0206] B: More than 3.0Ω and less than 6.0Ω
[0207] C: More than 6.0Ω and less than 10.0Ω
[0208] D: more than 10.0Ω
[0209] [Adhesion]
[0210] The adhesive strength (N / cm) of the connection structure at room temperature was measured using a universal tensile tester (Tensilon UTM-4, manufactured by TOYO BALDWIN KABUSHIKI KAISHA, peel strength 50 mm / min). The adhesive strength was evaluated into four levels according to the following criteria.
[0211] A: 10.0N / cm or more
[0212] B: 8.0 N / cm or more and less than 10.0 N / cm
[0213] C: 6.0 N / cm or more and less than 8.0 N / cm
[0214] D: less than 6.0N / cm
[0215] [Peeling area]
[0216] The degree of peeling of the connection portion was evaluated by the same method and criteria as those used in the evaluation of salt water resistance.
[0217] [Table 4]
[0218]
[0219] Explanation of symbols
[0220] 1A, 1B-adhesive film, 2-adhesive layer, 3-adhesive component, 4-conductive particles, 5-first adhesive layer, 6-second adhesive layer, 10-connecting structure, 11-first substrate, 12-first electrode, 13-first circuit component, 14-second substrate, 15-second electrode, 16-second circuit component, 17-connecting portion.
Claims
1. An adhesive composition comprising a radical polymerizable compound, a radical polymerization initiator, a compound having a nitrogen-containing aromatic heterocycle, and particles containing at least one metal compound selected from the group consisting of metal hydroxides and metal oxides.
2. The adhesive composition according to claim 1, wherein The nitrogen-containing aromatic heterocyclic ring is at least one selected from the group consisting of a pyrazole ring, an imidazole ring, a triazole ring, a tetrazole ring, a thiazole ring, a thiadiazole ring, an oxazole ring and a pyrimidine ring.
3. The adhesive composition according to claim 1 or 2, wherein: The metal compound includes at least one selected from the group consisting of aluminum, magnesium, zirconium, bismuth, calcium, tin, manganese, antimony, and titanium.
4. The adhesive composition according to any one of claims 1 to 3, wherein The particles include the metal hydroxide.
5. The adhesive composition according to any one of claims 1 to 4, wherein: The total content of the compound having a nitrogen-containing aromatic heterocyclic ring and the content of the particles is 0.1 parts by mass or more and 5 parts by mass or less relative to 100 parts by mass of the total amount of the radical polymerizable compound. 6 . The adhesive composition according to claim 1 , further comprising conductive particles. 7 . An adhesive film comprising an adhesive layer comprising the adhesive composition according to claim 1 .
8. A connection structure comprising: A first circuit component having a first electrode; a second circuit component having a second electrode; and a connecting portion disposed between the first circuit component and the second circuit component and electrically connecting the first electrode and the second electrode to each other; The connecting portion comprises a cured product of the adhesive composition according to any one of claims 1 to 6.
9. A method for manufacturing a connection structure, comprising the following steps: The adhesive composition according to any one of claims 1 to 6 is interposed between a first circuit component having a first electrode and a second circuit component having a second electrode, and the first circuit component and the second circuit component are thermally compressed to electrically connect the first electrode and the second electrode to each other.